2017
DOI: 10.1055/s-0037-1598654
|View full text |Cite
|
Sign up to set email alerts
|

Parameters Influencing Tracheostomy Decannulation in Patients Undergoing Rehabilitation after severe Acquired Brain Injury (sABI)

Abstract: Introduction  Tracheostomy weaning in patients who suffered a severe acquired brain injury is often a challenge and decannulation failures are not uncommon. Objective  Our study objective is to describe the decannulation failure rate in patients undergoing rehabilitation following a severe acquired brain injury (sABI); to describe the factors associated with a successful tube weaning. Methods  We conduct a retrospective analysis of charts, consecutively retrieved considering a 3-year window. Variables analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 34 publications
(122 reference statements)
2
21
0
1
Order By: Relevance
“…71 It is important to remember that it is a hypothetical score and requires validation in daily practice. Two recent studies, a systematic review and a retrospective study, associated positive spontaneous cough in patients with TBI as a predictor of the success of decannulation, 72,73 a result that is consistent with the literature reviewed. In general, decannulation is more often individualized than protocol based.…”
Section: Decannulation Protocolsupporting
confidence: 78%
“…71 It is important to remember that it is a hypothetical score and requires validation in daily practice. Two recent studies, a systematic review and a retrospective study, associated positive spontaneous cough in patients with TBI as a predictor of the success of decannulation, 72,73 a result that is consistent with the literature reviewed. In general, decannulation is more often individualized than protocol based.…”
Section: Decannulation Protocolsupporting
confidence: 78%
“…We did not find an association between successful decannulation and demographic factors, etiology of injury, injury characteristics, or timeline from initial injury to selected events, although there was a trend toward a younger mean age in the unsuccessful decannulation group. We did not look at the relationship between findings on imaging or Glasgow Coma Scale and decannulation, which has been reported in other studies . Given our small sample size, further studies are needed to determine what demographic factors or factors related to underlying diagnosis may be associated with decannulation success as this could help to tailor decannulation protocols to specific patient populations.…”
Section: Discussionmentioning
confidence: 93%
“…other studies. [16][17][18] Given our small sample size, further studies are needed to determine what demographic factors or factors related to underlying diagnosis may be associated with decannulation success as this could help to tailor decannulation protocols to specific patient populations.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have investigated predictors of decannulation in subjects with acquired brain injury. However, many studies are of poor quality (eg, small study populations, or the use of univariate analyses), 4,5,7,8,20,[27][28][29] thus limiting the conclusions that may be drawn from those studies. 30 A few recent studies have investigated the prediction of decannulation in larger study populations of subjects with neurological diseases and acquired brain injury using routinely gathered clinical data and applying multivariable analytical methods.…”
Section: Discussionmentioning
confidence: 99%
“…3 By using clinical data, which are routinely gathered as part of everyday practice, it is possible to develop prognostic models that can be implemented directly into clinical practice because they do not require any changes in practice or the purchase of new medical equipment. 3 Several small studies have reported that swallowing capability, [4][5][6] coughing, 5,7 and early rehabilitation 8 were predictors of decannulation in subjects with acquired brain injury. However, these studies are of poor quality and do not provide an applicable prognostic tool.…”
Section: Introductionmentioning
confidence: 99%